Factors Influencing Muslim Customer Loyalty: The Mediating Effect of Muslim Customer Satisfaction in Indonesia - Devy Leony Olyvia; Darwanto Darwanto (Shirkah: Journal of Economics and Business, 2023)
McDonald's held the second position in the Top Brand Index for five consecutive years from 2015 to 2020 conducted by Frontier Consulting Group, with participation from customers in eight major cities in Indonesia, including Semarang city. McDonald's experienced a decline in customer loyalty, which poses a challenge for the restaurant to maintain its customer base and attract new customers. Therefore, this research aims to examine the factors that influence Muslim customers' loyalty to McDonald's. The study focuses on Muslim customers with McDonald's subscriptions in Semarang City, with a sample of 144 respondents. The analysis technique used was the Structural Equation Model-AMOS. The study reveals that halal labeling, product quality, and Muslim customer satisfaction have a significant effect on Muslim customer loyalty. The quality and price of the product have a significant effect on Muslim customer satisfaction. Muslim customer satisfaction as an intervening variable cannot mediate all variables on Muslim customer loyalty. Hence, producers should focus on products ofÂ al-tayyibat.